Climate-induced year-class fluctuations of whitemouth croaker Micropogonias furnieri (Pisces, Sciaenidae) in the Río de la Plata estuary, Argentina-Uruguay - Acha, Eduardo Marcelo (2012)
The whitemouth croaker, Micropogonias furnieri, is exploited by coastal fisheries in the Plata estuary. Its age structure shows the predominance of certain year classes, which are indicative of recruitment variability. The estuary is affected by river discharge variations associated with climatic signals (El Niño Southern Oscillation and others). We hypothesize that recruitment may correlate: (i) negatively with runoff (low runoff would promote the stronger retention of ichthyoplankton); (ii) positively with temperature (higher temperatures should enhance larvae survivorship and ⁄ or expand the spawning season); and (iii) positively with the wind zonal component (stronger onshore winds should facilitate the retention of ichthyoplankton). A time series of the relative cohort strengths was constructed for the 1938–2000 period from the age frequencies based on otolith readings. We performed a spectral analysis of the biological and physical series, and we searched for co-movements between them, which suggested the presence of mechanistic links. The results showed co-movements for recruitment, runoff and air temperature series at approximately 6.5, 3.4 and 2.4 yr; the temperature reinforced the runoff effects on recruitment at the 6.5- yr peak, and it weakened them at the 3.4- and 2.4-yr peaks. Wind variability was not relevant for the time scales studied. To explore the mechanisms of retention, we modeled the effects of the runoff fluctuations on the dispersal of the eggs. Both the statistical and modeling results supported the hypothesis that the effects of extreme river discharges on retention may regulate croaker recruitment by promoting high (low) recruitment during low (high) discharge periods.